Measures of respiratory inductance plethysmography (RIP) in children with neuromuscular disease. Issue 9 (12th July 2018) - Strang, Abigail; Ryan, Lauren; Rahman, Tariq; Balasubramanian, Sona; Hossain, Jobayer; Heinle, Robert; Shaffer, Thomas H.
Abstract: Background: Pulmonary function testing (PFT) is essential for the clinical assessment of respiratory problems. Respiratory inductance plethysmography (RIP) is a non‐invasive method of PFT requiring minimal patient cooperation. RIP measures the volumetric change in the ribcage and abdomen, from which work of breathing (WOB) indices are derived. WOB indices include: phase angle (Ф), percent ribcage (RC%), respiratory rate (RR), and labored breathing index (LBI). Heart rate (HR) is collected separately. Aim: The goal of this study was to assess the utility of a newly developed RIP system, the pneu RIP, in an outpatient clinic setting in children with neuromuscular (NM) disease. Method: The pneu RIP system measures and displays the WOB indices in real‐time on an iPad display. Forty‐three subjects, 22 NM patients and 21 healthy children (ages: 5‐18 years) were enrolled. Results: Patients' means showed an increase of 119.8% for Ф, 15.7% for LBI, and 19.9% for HR compared with healthy subjects, when adjusted for age and gender. The study found significant differences between the mean values of the healthy subjects and patients in Ф ( P = 0.000), LBI ( P = 0.001), and HR ( P = 0.001). No differences were noted for RC% and RR between groups. Data for Ф in NM patients were diffusely distributed as compared with healthy subjects based on analysis of histograms. Conclusion: Non‐invasive pneu RIP testing provided instantaneous PFT results. As compared to healthy subjects, NM patients showed abnormal results with increased markers of thoracoabdominal asynchrony, WOB indices, and biphasic breathing patterns likely resulting from NM weakness.